Efgartigimod non-responders after the first treatment cycle in generalized myasthenia gravis: a retrospective analysis of predictive factors - Niu, Zhenyu; Wang, Jianchun; Ren, Jingru; Liu, Ran; Guo, Jing; Zhang, Nan; Zheng, Yiming; Hao, Hongjun; Gao, Feng; Jin, Haiqiang (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to identify predictors of suboptimal response to efgartigimod in patients with generalized myasthenia gravis (gMG).MethodsIn this single-center retrospective study, 35 gMG patients treated with efgartigimod were categorized into responders (n = 25) and non-responders (n = 10). Responders were defined by a reduction of >2 points in MG-ADL or >3 points in QMG score after one cycle, whereas non-responders showed improvement below these thresholds and subsequently responded to eculizumab. Demographic, clinical, and serological features were compared using univariate and multivariate analyses.ResultsNon-responders had higher baseline gross motor and respiratory sub-scores. Univariate analysis revealed that thymoma, non-thymoma tumors, thyroid disease, and other autoimmune diseases were more common in non-responders. Multivariate analysis indicated that combinations of these factors were associated with a high predicted probability of poor response (up to 97.9%).InterpretationComorbidities including thymoma, other tumors, thyroid disease, and additional autoimmune disorders may predict reduced response to efgartigimod in gMG patients. Systematic evaluation of these factors could help optimize treatment selection.